2001
DOI: 10.1038/ng0501-53
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin–sensitive isoforms of lymphoid enhancer factor-1 are selectively expressed in colon cancer

Abstract: Constitutive activation of the Wnt signaling pathway is a root cause of many colon cancers. Activation of this pathway is caused by genetic mutations that stabilize the beta-catenin protein, allowing it to accumulate in the nucleus and form complexes with any member of the lymphoid enhancer factor (LEF1) and T-cell factor (TCF1, TCF3, TCF4) family of transcription factors (referred to collectively as LEF/TCFs) to activate transcription of target genes. Target genes such as MYC, CCND1, MMP7 and TCF7 (refs. 5-9)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
291
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(308 citation statements)
references
References 21 publications
16
291
0
1
Order By: Relevance
“…LEF1 (Hovanes et al, 2001), MMP7 (Brabletz et al, 1999), cyclin D1 (Tetsu and McCormick, 1999) and CD44 (Wielenga et al, 1999) are all reported to be direct or indirect targets of b-catenin-TCF/LEF, confirming that Wnt signaling is blocked by SFRP2 in SNU638 cells (Table 2). We also found that significant numbers of genes related to cellular proliferation, growth or apoptosis are repressed or induced by SFRP2.…”
Section: Changes In Gene Expression Profiles Induced By Overexpressiomentioning
confidence: 67%
“…LEF1 (Hovanes et al, 2001), MMP7 (Brabletz et al, 1999), cyclin D1 (Tetsu and McCormick, 1999) and CD44 (Wielenga et al, 1999) are all reported to be direct or indirect targets of b-catenin-TCF/LEF, confirming that Wnt signaling is blocked by SFRP2 in SNU638 cells (Table 2). We also found that significant numbers of genes related to cellular proliferation, growth or apoptosis are repressed or induced by SFRP2.…”
Section: Changes In Gene Expression Profiles Induced By Overexpressiomentioning
confidence: 67%
“…Wnt signaling regulates various developmental processes and can lead to cancer formation. MMP7 has been reported overexpressed in human gastric cancers Yamamoto et al, 2004) and colorectal cancers (Matsushima et al, 1998;Hovanes et al, 2001). Recently, Chung et al conducted an IHC analysis of regulation of the b-catenin signaling pathway on a breast cancer tissue microarray.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has suggested the existence of another pathological vicious cycle involving b-catenin in CRC. In addition to its effects on gastrin and on the expression of other target genes, Hovanes et al (2001) reported that LEF-1, one of the transcriptional partners of bcatenin, is likewise a target gene of b-catenin/TCF-dependent transcription.…”
Section: Discussionmentioning
confidence: 99%